PA28αβ: The Enigmatic Magic Ring of the Proteasome? - Cascio, Paolo (MDPI, 2014)
PA28αβ is a γ-interferon-induced 11S complex that associates with the ends of the 20S proteasome and stimulates in vitro breakdown of small peptide substrates, but not proteins or ubiquitin-conjugated proteins. In cells, PA28 also exists in larger complexes along with the 19S particle, which allows ATP-dependent degradation of proteins; although in vivo a large fraction of PA28 is present as PA28αβ-20S particles whose exact biological functions are largely unknown. Although several lines of evidence strongly indicate that PA28αβ plays a role in MHC class I antigen presentation, the exact molecular mechanisms of this activity are still poorly understood. Herein, we review current knowledge about the biochemical and biological properties of PA28αβ and discuss recent findings concerning its role in modifying the spectrum of proteasome’s peptide products, which are important to better understand the molecular mechanisms and biological consequences of PA28αβ activity.